Intervention strategies to prevent mental health problems and improve resilience in employed parents from conception until the child is 5 years of age: a scoping review - Neeltje Crombag; Bieke Bollen; Eline Vancoppenolle; Thomas Vandendriessche; Dagmar Versmissen; Martha Paisi; Jill Shawe; Susan Garthus-Niegel; Annick Bogaerts (BMC Pregnancy and Childbirth)
Abstract Aim To understand the extent and type of evidence in relation to the effectiveness of intervention strategies targeting working pregnant women, and their partners, for the prevention of mental health problems (depression, anxiety) and improving resilience, from conception until the child is 5 years of age. Methods A scoping review was conducted searching Pubmed (including Medline), Embase, Web of Science Core Collection and Scopus. Inclusion criteria were based on population (employed parents), context (from -9 months to 5 years postpartum) and concept (mental health problems, resilience and prevention/ preventative interventions). Results Of the 17,699 papers screened, 3 full text papers were included. Studies focused on intervention strategies for working parents which showed a relationship with a reduction in mental health problems (depression and/or anxiety). The intervention strategies extracted from the literature referred to ‘social support’. Social support provided by both the social and the work environment correlated with prenatal stress and depressive symptoms in the postpartum period, and supports a healthy work-family balance. Conclusion Social support seems to have a positive association with the reduction of mental health problems. However, there are still important gaps in the literature such as a lack of RCT designs to test effectiveness of interventions and systematic reviews. Findings from this study may provide a roadmap for future research to close these gaps in knowledge.